Reliability and validity of match performance analysis in soccer : a multidimensional qualitative evaluation of opponent interaction - Tenga, A. P. C. (2010)
Match performance analysis is widely used as a method for studying technical, tactical and physical aspects of player and team performance in a soccer match. Therefore, ensuring the validity and reliability of the collected data is important for match performance analysis to meet its intents and purposes effectively. However, most studies on soccer match performance use unidimensional frequency data based on analyses done in isolation from the match context. In addition, reliability studies reported previously are generally small and with significant methodological limitations. Therefore, the main aim of this thesis was to develop, test the reliability of, and apply a new method for team match performance analysis in soccer which includes an assessment of opponent interaction by using categorical data based on multidimensional qualitative evaluation.